2001
DOI: 10.1063/1.1376411
|View full text |Cite
|
Sign up to set email alerts
|

Generalized proximity effect model in superconducting bi- and trilayer films

Abstract: This paper presents a general model for calculating the density of states and the Cooper pair potential in proximised superconducting bi-and trilayer films. It is valid for any kind of bilayer S 1 -S 2 , whatever the quality of the materials S 1 and S 2 , the quality of the S 1 -S 2 interface and the layer thicknesses. The trilayer model is valid for a thin S 3 layer, whereas the other two layers have arbitrary thicknesses. Although the equations of the dirty limit are used, it is argued that the model stays v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…This energy corresponded to the edge of the gap in the bulk superconducting Ta, ⌬ Ta , and problems arose because of the strong peak in density of states inside the bilayered structure. 30 Fortunately, by chance, the 3⌬ active region threshold in our proximized Ta/Al structure at 0.72 meV coincided almost exactly with the bulk gap value in Ta. Hence, for qp's in the energy region ⌬Ͻ⑀Ͻ3⌬, we showed that all the relevant important parameters could be calculated within the framework of a proxy BCS model, in which characteristic times 0 and ph are simply scaled with the proximized gap according to 0 ϭ 0,Al (⌬ Al /⌬) 3 and ph ϭ ph,Al (⌬ Al /⌬).…”
Section: A Experimental Detailssupporting
confidence: 57%
“…This energy corresponded to the edge of the gap in the bulk superconducting Ta, ⌬ Ta , and problems arose because of the strong peak in density of states inside the bilayered structure. 30 Fortunately, by chance, the 3⌬ active region threshold in our proximized Ta/Al structure at 0.72 meV coincided almost exactly with the bulk gap value in Ta. Hence, for qp's in the energy region ⌬Ͻ⑀Ͻ3⌬, we showed that all the relevant important parameters could be calculated within the framework of a proxy BCS model, in which characteristic times 0 and ph are simply scaled with the proximized gap according to 0 ϭ 0,Al (⌬ Al /⌬) 3 and ph ϭ ph,Al (⌬ Al /⌬).…”
Section: A Experimental Detailssupporting
confidence: 57%
“…This behavior markedly differs from the Ambegaokar-Baratoff prediction 11 and is expected for tunnel junctions embedding an interlayer like the present. 12,13 In order to validate our temperature calibration and rule out spurious overheating in the small island we also measured the I c ͑T bath ͒ dependence on similar junctions fabricated on a large-volume Al electrode, i.e., device C shown in Fig. 1͑d͒ ͑open squares͒.…”
Section: (S)mentioning
confidence: 99%
“…1,2 Over the last few years both the quality of the devices fabricated and the understanding of the relevant physical processes have improved greatly. Notable among the latter are the proximity effect, which determines the properties of the bilayer electrodes commonly used, [3][4][5] the various diffusion and loss mechanisms which limit the energy resolution of a STJ, 6,7 and the details of the quasiparticle interactions through which the overall performance of the detector is modeled. [8][9][10] In this article, we describe a major advance in the treatment of quasiparticle dynamics, which is essential for modeling the latest generation of low-gap, multitunneling STJs designed to operate at mK temperatures.…”
Section: Introductionmentioning
confidence: 99%